2018
DOI: 10.1152/ajpheart.00727.2017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cerebral autoregulation is impaired during submaximal isometric handgrip in patients with heart failure

Abstract: The incidence of neurological complications, including stroke and cognitive dysfunction, is elevated in patients with heart failure (HF) with reduced ejection fraction. We hypothesized that the cerebrovascular response to isometric handgrip (iHG) is altered in patients with HF. Adults with HF and healthy volunteers were included. Cerebral blood velocity (CBV; transcranial Doppler, middle cerebral artery) and arterial blood pressure (BP; Finometer) were continuously recorded supine for 6 min, corresponding to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…The time course of and the amount of the evoked CBFV achieved by our setting corresponds to other motor tasks evoked flow studies targeting NVC insofar as flow is evoked bilaterally, remains elevated as long as the stimulus is present, and an attenuation does not ensue, a BP increase occurs comparably to those observed in NVC studies (Caldas et al 2018, Giller et al 2000, Llwyd et al 2017, Maggio et al 2013, Nikolic et al 2015. In contrast to these reports on NVC, however, our continuous motor task showed changes in the LF range (% /mmHg) and in the VLF range (phase) which are consistent with a disturbed dynamical CA (dCA, Zhang et al1998, Panerai et al 1999, Panerai et al 2001, Serrador et al 2005.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The time course of and the amount of the evoked CBFV achieved by our setting corresponds to other motor tasks evoked flow studies targeting NVC insofar as flow is evoked bilaterally, remains elevated as long as the stimulus is present, and an attenuation does not ensue, a BP increase occurs comparably to those observed in NVC studies (Caldas et al 2018, Giller et al 2000, Llwyd et al 2017, Maggio et al 2013, Nikolic et al 2015. In contrast to these reports on NVC, however, our continuous motor task showed changes in the LF range (% /mmHg) and in the VLF range (phase) which are consistent with a disturbed dynamical CA (dCA, Zhang et al1998, Panerai et al 1999, Panerai et al 2001, Serrador et al 2005.…”
Section: Discussionsupporting
confidence: 70%
“…When CA fails an additional metabolic mechanism helps to keep oxygen concentration in the needed range by increasing the oxygen extraction rate as increasing the amount of the oxygen concentration released from hemoglobin (Leenders et al 1999). In pathological conditions such as acute stroke the coordinated overlapping of these mechanisms seems to be disturbed (Caldas et al 2018, Maggio et al 2013, Reinhard et al 2012, Rivera-Lara et al 2017) which might be relevant for an early start of rehabilitation (Coleman et al 2017, Li et al 2018, Chi et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral blood flow (CBF) is the combined result of BP, metabolic, and neuronal regulatory influences. In recent years, the influence of vaso-neural coupling (VNC) on CBF was determined to be a relevant contributor which can be disturbed even when cerebral autoregulation remains intact (Salinet et al, 2013, 2015; Caldas et al, 2018). To assess the dynamics of CA (dCA), applying a transfer function analysis (TFA) on the relationship between BP and CBFV is the most frequently used approach nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…When applied over 5-min recording periods, the phase and gain results are reliable, and phase is more robust than gain for the grading of CA capabilities (Claassen et al, 2016; Sanders et al, 2018). Most VNC studies used short task periods (≤60 s) to investigate VNC (Chance et al, 1993; Obrig et al, 2000; Salinet et al, 2013, 2015; Caldas et al, 2018), and are, therefore, unsuitable for assessing TFA (Claassen et al, 2016). In addition to the TFA of the BP-CBFV macrocirculatory relationship, the TF analyses of the dynamics of the interaction between BP and [oxHb], as well as of [deoxHb] (microcirculatory response), have also shown that it is possible to grade CA failure (Reinhard et al, 2006; Cheng et al, 2012; Elting et al, 2018).…”
Section: Introductionmentioning
confidence: 99%